Analysis and design deep foundation for the national_ hospital street in nablus - Mosab adnan debas; Abdalrahman ammr sabha; Mousab Mousa marei; Waed Jamal Saed (My University, 2022)
Retaining structures include various types of structures among them the use of sheet pile walls and braced cuts. Sheet pile walls and braced cuts are generally used for retaining the sides of cuts made in earth, in water front structures, dams, cofferdams and other purposes. sheet piles and braced cuts have several advantages compares with other retaining structures especially when we have limited access in the are of construction. Our project consists of designing a proper retaining structure for an area in the center of Nablus city. This area has very limited accessibility and a very dense traffic. Therefore We decided to use either sheet pile walls or braced cuts system. Our project will be devoted to study and compare between these two options in the analysis and design. To achieve this goal we will study the site and its soil condition and problems.